The Effect of Waste Cooking Oil Administration on Spermatogenic Cells in Male Mice (Mus musculus) - Sari, Dewa Ayu Candranita Kerthy; I Made Oka Negara; I Gusti Ngurah Pramasemara (Indonesian Andrology and Biomedical Journal, 2025)
Background : The high consumption of fried foods in Indonesia leads to the common practice of repeatedly using cooking oil, transforming it into waste cooking oil (in Indonesian called “minyak jelantah). This oil undergoes chemical changes that generate compounds like reactive oxygen species (ROS), which are known to induce oxidative stress and are implicated in male infertility by disrupting spermatogenesis. Objective : This study aimed to investigate the effect of waste cooking oil administration on the number of spermatogenic cells (spermatogonia, primary spermatocytes, and spermatids) in the testes of male mice (Mus musculus). Methods : This experimental study used a post-test-only control group design. Fourteen male BALB/c mice were randomly divided into a control group (n=7), administered 0.2 ml/day of aquades, and a intevention group (n=7), administered 0.2 ml/day of waste cooking oil (palm oil heated 8 times at 180°C) for 36 days via oral sonde. After the intervention period, the mice were euthanized, and their testes were extracted for histological preparation with Hematoxylin-Eosin (H&E) staining. The number of spermatogenic cells was counted under a microscope across four fields of view. Data were analyzed using an Independent T-test. Results : Consecutively mean number of the spermatogonia, prymary spermatocyte and spermatids in the control group are 51,98 ± 1,60; 64,50 ± 2,14; 81,31 ± 3,04. Meanwhilem, Consecutively mean number of the spermatogonia, prymary spermatocyte and spermatids in the intervention group are 28,93 ± 3,20; 39,31 ± 3,57; 45,25 ± 3,97. Which mean, the mean number of spermatogenic cells was significantly lower in the intervention group compared to the control group Conclusion : The administration of waste cooking oil significantly reduces the population of spermatogenic cells including spermaogonia, prymary spermatocyte, and spermatid cells in male mice, indicating a detrimental effect on spermatogenesis. Keywords : Waste Cooking Oil, Spermatogenic Cells, Spermatogenesis, Oxidative Stress.